DFT insight into the oxygen reduction reaction (ORR) on the Pt₃Co(111) surface - Matsutsu, Molefi (Centre for Catalysis Research, 2016)
Proton exchange membrane fuel cells (PEMFC) are identified as future energy conversion devices, for application in portable and transportation devices. The preferred catalyst for the PEMFC is a Pt-catalyst. However, due to the slow oxygen reduction reaction (ORR) kinetics, high Pt loadings have to be used. The high Pt loadings lead to high costs of the PEMFC. Pt-Co alloys have been identified as catalysts having higher ORR activity higher than of a Pt-catalyst. Therefore, in the present study, the Density Functional Theory (DFT) technique is used to gain fundamental insight into the ORR on the Pt₃Co(111) surface. The calculations have been performed using the plane wave based code, the Vienna ab-initio Simulation Package (VASP). DFT spin-polarized calculations, utilizing the GGA-PW91 functional, have been used to study the adsorption of the ORR intermediates, viz. O₂, O, OOH, OH, H₂O and HOOH on the Pt₃Co(111) surface. The results obtained on the Pt₃Co(111) surface are compared to the results obtained on the Pt(111) surface. The adsorption strength of the ORR intermediates has been shown to be affected by the presence of Co to varying extents on the Pt₃Co(111) surface relative to adsorption on the Pt(111) surface. The most strongly stabilised ORR intermediate on the Pt₃Co(111) surface relative to adsorption on the Pt(111) surface is O: on the Pt₃Co(111) surface O is 0.45 eV more strongly adsorbed than on the Pt(111) surface. The least affected ORR intermediate is H₂O: H₂O adsorption on the Pt₃Co(111) surface is 0.20 eV more stable than on the Pt(111) surface. The energetically favorable, i.e. most strongly bound adsorption configurations for all the ORR intermediates involves a configuration in which the ORR intermediate is bonded to a surface Co atom. Therefore, the surface Co atom stabilizes the adsorption of the ORR intermediates, relative to adsorption on the Pt(111) surface. Coadsorbed configurations have been used to study the formation and dissociation of the ORR intermediates. From the coadsorption studies, it is shown that there is an energy cost associated with moving the adsorbates from their lowest energy sites, while separately adsorbed, to the higher energy coadsorbed state, prior to reaction. Hence, adsorbate-adsorbate interactions are expected to destabilize the coadsorbed state at the coverages considered in the present study. The Climbing Image Nudged Elastic Band (CI-NEB) method has been used to locate the transition states and to calculate the activation energies of the different elementary reaction steps. The calculated dissociation reaction activation energies for the Pt₃Co(111) surface are found to be lower than the dissociation activation energies calculated on the Pt(111) surface. The most lowered dissociation activation energy is for the dissociation of O₂: on the Pt₃Co(111) surface the activation energy is 0.08 eV, whilst on the Pt(111) surface the activation energy is 0.59 eV. For the hydrogenation reaction steps, only the hydrogenation of O to form OH occurs with a lower activation energy of 0.86 eV on the Pt₃Co(111) surface, compared to 0.95 eV on the Pt(111) surface. For other hydrogenation reaction steps, the activation energies on the Pt₃Co(111) surface are higher than those on the Pt(111) surface. Based on the calculated activation energies of the elementary ORR reaction steps, the dissociative and the O-assisted H₂O dissociation mechanisms are identified as the mechanisms most likely to be dominant on the Pt₃Co(111) surface, due to having lower activation energies relative to the associative mechanisms. For both mechanisms, the reaction step with the highest activation energy is the step involving O, i.e. O hydrogenation to form OH for the dissociative mechanism, and the O* + H₂O* --> 2OH* reaction for the O-assisted H₂O dissociation mechanism. Thus, the reaction step involving the reaction of the strongly adsorbed O species, is identified as the potential rate limiting step of the ORR. Both the dissociative and the O-assisted H₂O dissociation mechanisms are expected to be in competition on the Pt₃Co(111) surface, since the potential rate limiting step for both mechanisms have similar activation energies. Hence, the preferred mechanism will depend on the relative abundances of the H species and H₂O on the Pt₃Co(111) surface. A microkinetic analysis would be need needed to fully account for concentration and entropic contributions to the rate of reaction for the different ORR elementary reaction steps.